Implementasi Akad Salam dalam Pengadaan Buku di Perpustakaan IAI AL-AZIS Indramayu Ditinjau dari Hukum Ekonomi Syariah - Rabbani Nabilah Al-Qudsi; Rizal Maulana; Irvan Iswandi (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study examines the implementation of the akad salam contract in book procurement at the IAI AL-AZIS Indramayu Library and its compliance with the principles of Islamic economic law. The research employs a qualitative approach, with data collected through observation, interviews, and documentation. The findings reveal that the implementation of the akad salam aligns with the library's standard operating procedures (SOP). The procurement process involves identifying needs, selecting books through e-commerce, and making upfront payments before delivery. The akad salam provides flexibility and ease in procurement, supported by online technology to enhance efficiency. Risk management is carried out through buyer reviews and communication with sellers, ensuring the quality of the books received matches the orders. From the perspective of Islamic economic law, the implementation of the akad salam meets the requirements, namely upfront payment for goods to be received later. Online book procurement at the IAI AL-AZIS Library also reflects transparency and efficiency. By applying the akad salam, the library can effectively provide the necessary academic references, adhere to Sharia principles, and leverage modern technology to support educational needs. This study highlights the significant role of the akad salam in ensuring efficiency and sustainability in Sharia-based book procurement.